The effect of cis-jasmone, jasmonic acid and methyl jasmonate on accumulation of anthocyanins and proanthocyanidins in seedlings of common buckwheat (Fagopyrum esculentum Moench) - Marcin Horbowicz; Halina Mioduszewska; Danuta Koczkodaj; Marian Saniewski (Acta Societatis Botanicorum Poloniae, 2011)
Effects of various jasmonates (methyl jasmonate, jasmonic acid, cis-jasmone) on anthocyanins and procyanidins content of, as well as on growth of common buckwheat (Fagopyrum esculentum Moench) seedlings were studied. The studied jasmonates were applied as solutions or vapors on four days seedlings, and the seedlings were grown during the next four days in day/night conditions (16/8 h). Afterwards anthocyanins and proanthocyanidins content, as well as elongation of primary roots and hypocotyls were measured. When applied as solutions cis-jasmone (JAS) stimulated the anthocyanins accumulation, but when used as vapors had tendency to decrease its accumulation in buckwheat hypocotyls. Jasmonic acid (JA) solutions slightly stimulated or had no effect on biosynthesis of anthocyanins in buckwheat hypocotyls, but used as vapors caused a decline of anthocyanins in buckwheat hypocotyls. Methyl jasmonate (MJ) clearly inhibited biosynthesis of anthocyanins in hypocotyls of buckwheat seedlings. The studied jasmonates had no influence on anthocyanins level in cotyledons of buckwheat seedlings, except cis-jasmone, which at the lowest solution concentration slightly enhanced biosynthesis of the pigments. Treatment of buckwheat seedlings with solutions of all jasmonates (10-8 M, 10-6 M and 10-4 M) had no influence on the growth of buckwheat hypocotyls. Contrary to that observation vapors of the growth regulators in concentrations 10-4 M, had a strong inhibitory effect on the growth of hypocotyls of buckwheat seedlings. Solutions of JA and MJ, as well as vapors of JA, MJ and JAS strongly inhibited the primary root growth of buckwheat seedlings, while JAS applied as solution had no such influence. MJ and JA caused much higher stimulation of proanthocyanidin biosynthesis in buckwheat hypocotyls than JAS.